(untitled) (Journal of the College of Basic Education, 2022)
Inertial collimator is one of the important techniques used for sorting aerosol particles for the purposes of this work. Inertial collimator was designed and implemented in local workshops. Generally, the required cutting ratio and collimator efficiency are controlled by many aerodynamic factors. In this study, the cutting ratio of 50% was chosen theoretically to be (1µm). The implemented collimator was tested using an optical particle counter (Climate CI 500) and the results showed that the collimator collection efficiency was close to 100% for particles (5 µm) or larger.